(untitled) (Journal of Pathology of Nepal, 2024)
Background: The safe transfusion of blood facilities is an essential component of an efficient, excellent healthcare sector. Unsafe blood transfusions can be a cause of transfusion-transmitted infections and can be lethal. The present study was conducted to find out the seroprevalence of HBsAg, HCV, HIV, malarial parasites, and syphilis in voluntary blood donors in a tertiary care center. Materials and methods: This prospective study was conducted at the blood bank of the Shri Mahant Indiresh Hospital, Dehradun. 16413 samples from all blood donations were screened for HBsAg, HCV, HIV 1 and 2, malaria, and syphilis. Samples were collected in vacutainers at the time of blood donation and screened for HIV 1and2, HBsAg, and HCV using the fourth-generation enzyme-linked immunosorbent assay technique. Syphilis was tested by Treponema antibodies using the VITROS Syphilis TPA Reagent Pack. Malaria was tested by pan malaria card, monoclonal anti-pan specific parasite lactate dehydrogenase antibody conjugated to colloidal gold, and another monoclonal anti-pan specific parasite lactate dehydrogenase antibody immobilized on a nitrocellulose strip in a thin line. Results: Out of 16413 blood donors 342(2.1%) were found to be seropositive and 16071 (97.9%) were found to be seronegative. The total number of donors, who were found positive for HBsAg/Anti HCV was 1 (0.3%). Out of the seropositive cases, HBsAg, HCV, HIV, and Syphilis infections constituted 28.9%, 27.5, 14.6, and 28.7% cases respectively. Conclusions: There is a need for the development and implementation of stringent donor selection and sensitive screening tests to reduce the risk of acquiring transfusion-transmitted illnesses.